2016
DOI: 10.2175/106143016x14696400494579
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Processes

Abstract: This review, for literature published in 2015, contains information related to membrane processes for municipal and industrial applications. This review is a subsection of the Treatment Systems section of the annual Water Environment Federation literature review and covers the following topics: pretreatment, membrane bioreactor (MBR) configuration, design, nutrient removal, operation, industrial treatment, anaerobic membrane systems, reuse, microconstituents removal, membrane technology advances, membrane foul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Neoh and co-workers recently studied membrane fouling and the associated energy demand for wastewater treatment processes, where they found the key factors to be resolved for the full exploitation of integrated membrane solutions for wastewater treatment processes [120]. In the same year, the annual water environment federation literature review confirmed a similar point as well [121]. Tan and co-workers developed a map that compares different fouling mitigation techniques with respect to the salinity of the influent.…”
Section: Foulingmentioning
confidence: 90%
“…Neoh and co-workers recently studied membrane fouling and the associated energy demand for wastewater treatment processes, where they found the key factors to be resolved for the full exploitation of integrated membrane solutions for wastewater treatment processes [120]. In the same year, the annual water environment federation literature review confirmed a similar point as well [121]. Tan and co-workers developed a map that compares different fouling mitigation techniques with respect to the salinity of the influent.…”
Section: Foulingmentioning
confidence: 90%
“…It can be found that the wastewater also contains polymer, which has a strong binding force with the membrane surface and would cause the membrane flux decline. Since sodium dodecylbenzenesulfonate (SDBS) is a surfactant that can effectively remove granular fouling [30], it was tested in the cleaning process. It can be found from Figure 5 that with 0.1% NaOH and 0.1% SDBS cleaning, more than 90% flux recovery was achieved.…”
Section: Investigation Of Pilot Test Parametersmentioning
confidence: 99%